1986
DOI: 10.2307/3213999
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual Galton–Watson branching processes with superadditive mating functions

Abstract: For a bisexual Galton–Watson branching process with superadditive mating function there is a simple criterion for determining whether or not the process becomes extinct with probability 1, namely, that the asymptotic growth rate r should not exceed 1. When extinction is not certain (equivalently, r > 1), simple upper and lower bounds are established for the extinction probabilities. An example suggests that in the critical case that r = 1, some condition like superadditivity is essential for ultimate extinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 12 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…One may cite as examples work on the extinction probability (e.g., Daley (1968), Hull (1982Hull ( , 1984, Bruss (1984), Daley et al (1986), or Alsmeyer and Rösler (2002)), the long term behaviour (e.g., Bagley (1986) or González andMolina (1996, 1997)), and inference problems (e.g., González-Fragoso (1995), Molina et al (1998), Alsmeyer and Rösler (1996), or González et al (2001)). Two interesting recent reviews are Hull (2003) and Haccou et al (2005).…”
Section: Pmentioning
confidence: 99%
“…One may cite as examples work on the extinction probability (e.g., Daley (1968), Hull (1982Hull ( , 1984, Bruss (1984), Daley et al (1986), or Alsmeyer and Rösler (2002)), the long term behaviour (e.g., Bagley (1986) or González andMolina (1996, 1997)), and inference problems (e.g., González-Fragoso (1995), Molina et al (1998), Alsmeyer and Rösler (1996), or González et al (2001)). Two interesting recent reviews are Hull (2003) and Haccou et al (2005).…”
Section: Pmentioning
confidence: 99%
“…Hence (F n ) n≥0 is also supercritical and its extinction probability q less than 1. A numerical study in [7] showed for the case where p F and p M are Poisson with mean 1.2 that the extinction probability ratio…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The bisexual Galton-Watson process with promiscuous mating (Z n ) n≥0 , shortly called promiscuous BGWP, is defined as follows: Consider a two sex population process (Z The formal definition of (Z Bisexual GWPs with various mating functions were introduced by Daley [6] and further investigated in a series of papers [5], [7], [8], [9]. The present article is a continuation of [1] where we compared in some detail the extinctive behavior of a promiscuous BGWP (Z n ) n≥0…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…This is not a severe constraint, since most mating functions considered in two-sex branching process theory are superadditive (see, e.g. Hull (1982) or Daley et al (1986)). …”
Section: Probability Generating Functionsmentioning
confidence: 99%
“…Several classes of discrete-time two-sex (bisexual) branching processes have been studied, including the bisexual GaltonWatson process (see Alsmeyer and Rösler (1996), (2002), Bagley (1986), Bruss (1984), Daley (1968), and Daley et al (1986)); processes with immigration (see González et al (2000), (2001), and Ma and Xing (2006)); in varying environments (see , (2004a)); and processes depending on the number of couples in the population (see Molina et al (2002Molina et al ( ), (2004bMolina et al ( ), (2006, and Xing and Wang (2005)). We refer the reader to Hull (2003) or Haccou et al (2005, pp.…”
Section: Introductionmentioning
confidence: 99%